Measuring User Satisfaction of Participant Reporting Information System Services at the Tanjung Morawa Branch of the Employment Social Security Administration Agency - Sibarani, Rheince; Rini, Endang Sulystia; Situmorang, Syafrizal Helmi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to use the End User Computing happiness (EUCS) approach to the Participant Reporting Information System (SIPP) service in order to ascertain and analyze the degree of user happiness. This study is based on the phenomenon of the reporting system's shift from a manual to an online one. Content, accuracy, format, usability, and timeliness are the dimensions that this research employs to measure user satisfaction. Using a quantitative technique, this research examines associations. The 273 participants who made up the population were personnel officials from the companies that were part of the BPJS Employment Tanjung Morawa Branch. This study drew from a total of 170 participants. A random sampling technique is employed, where each sample has an equal chance of being chosen. A linear regression analysis was performed on the collected data.